2004
DOI: 10.1002/anie.200460263
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Poly(carbon suboxide) by Small‐Angle X‐ray Scattering

Abstract: Band substances: The polymerization of C3O2 (see picture left, at −10 °C) into a red‐brown, solid polymer (right) having identical composition has been known for almost 100 years. However, the constitution of the polymer remained unknown. Small‐angle X‐ray scattering studies of the dissolved polymer show that it forms a stiff bandlike molecule with approximately 40 monomeric units, thus confirming the predicted bandlike structure with condensed α‐pyrone rings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Already small amounts of water increase solubility drastically. A determination of the molar mass and molecular shape of the dissolved polymer in DMF/H 2 O by small‐angle X‐ray scattering has recently been performed 21…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Already small amounts of water increase solubility drastically. A determination of the molar mass and molecular shape of the dissolved polymer in DMF/H 2 O by small‐angle X‐ray scattering has recently been performed 21…”
Section: Methodsmentioning
confidence: 99%
“…Consequently more recent experimental evidence12 questions the simple poly‐α‐pyrone model. In addition it has been shown by small angle X‐ray scattering on solutions of poly(carbonsuboxide)21 that the molar mass has been greatly underestimated in earlier work 8. 12, 13…”
Section: Introductionmentioning
confidence: 96%
“…Structure of HCN polymer is one possible among others (see Minard et al 1998 for more structures). Structure of carbon suboxide polymers proposed by Ballauff et al (2004) specifically characteristic of POM: the regular pattern observed is only the signature of a mixture of organic molecules composed of C, H, O, N atoms. Thus, even if the observed spectrum is not sufficient to establish its presence definitively, the presence of POM in cometary nucleus and dust particles cannot be ruled out at this stage.…”
Section: Origin Of H 2 Comentioning
confidence: 99%
“…Small-angle X-ray scattering analysis of poly(carbon suboxide), (C 3 O 2 ) n confirms that in solution the structure is poly(a-pyronic), the value of n (#40) suggests a one-dimensional bandlike structure. 82 The [5,6]-open isomer of C 60 O dimerises readily to give a C 2 symmetric adduct C 120 O 2 , in which the cages are linked by two single bonds between the sp 3 hybridised carbons adjacent to the oxygen atoms. 83 The absorption spectrum of C 120 O 2 in toluene is red-shifted relative to C 120 , while photodissociation of the dimer occurs under comparatively mild conditions. ]…”
Section: Oxygenmentioning
confidence: 99%